AKULTURASI DAN PERKEMBANGAN ISLAM DI INDONESIA DALAM SISTEM KALENDER: Kalender Jawa-Islam - Indana Zuyyina Illiyyin; Maulidia, Rinata (UIN ALAUDDIN MAKASSAR, 2021)
This research is based on the many cultures in Indonesia, especially the influence of culture in Islam with various fields. One of these fields is the calendar, acculturation of Islamic culture in the calendar system which is seen that cultural acculturation in Islam greatly affects various fields, especially the calendar system. The acculturation of Islamic culture affects the calendar system and these events occur especially in Indonesia. Indonesia has a lot of acculturation of Islamic culture, this happens because before Islam came, there were already many indigenous cultures, religions (Hindu-Buddhist), and others. In this journal, we will discuss about one of the acculturation of Islamic culture that entered Indonesia, namely the calendar system.